2010
DOI: 10.7763/ijesd.2010.v1.48
|View full text |Cite
|
Sign up to set email alerts
|

Awareness about Bio-Medical Waste Management among Health Care Personnel of Some Important Medical Centers in Agra

Abstract: -The proper handling and disposal of Bio-medical waste (BMW) is very imperative. There are well defined set of rules for handling BMW worldwide. Unfortunately, laxity and lack of adequate training and awareness, in execution of these rules leads to staid health and environment apprehension. In this research paper, awareness about bio-medical waste (BMW) management rules among health care personnel of some important health care facilities in Agra is evaluated. In the present study, health care facilities are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
70
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 8 publications
14
70
4
4
Order By: Relevance
“…Malini ve ark. çalışmasıyla aynı bölgede yapılan diğer araştırmalarda da benzer sonuçların olduğu görülmektedir (18)(19)(20)(21). Bununla beraber Uddin ve arkadaşlarının çalışmasında ise hemşirelerin yanlızca %6,4'ünün enfekte atıklarla ilgili soruya tam olarak doğru yanıt verdiği belirlenmiştir(5).…”
Section: Discussionunclassified
“…Malini ve ark. çalışmasıyla aynı bölgede yapılan diğer araştırmalarda da benzer sonuçların olduğu görülmektedir (18)(19)(20)(21). Bununla beraber Uddin ve arkadaşlarının çalışmasında ise hemşirelerin yanlızca %6,4'ünün enfekte atıklarla ilgili soruya tam olarak doğru yanıt verdiği belirlenmiştir(5).…”
Section: Discussionunclassified
“…and other auxiliaries of Haryana [11] and Jaipur [12] were less knowledgeable about Bio Medical Waste Disposal compared with this study.…”
Section: Methodsmentioning
confidence: 40%
“…Earlier studies conducted in India, conclude that most of the dentist's and dental auxiliaries have poor knowledge of BMW disposal. [1,[9][10][11][12] Against this background, a study has undertaken to assess knowledge, and practice adopted by dental practitioners and auxiliaries from Pune regarding BMW disposal, which is vital for control of cross infection.…”
Section: Discussionmentioning
confidence: 99%
“…Such questions are easy to analyze and may achieve a quicker response from participants. 7 The results of present study showed that knowledge regarding BMW management was poor among health care personnel. Very few had excellent knowledge (p <0.05).…”
Section: Discussionmentioning
confidence: 89%
“…3 Efforts of health care personnel may seem small, but each step taken by them can build a base of sound behavior and thinking, which are necessary for the success of whole scenario. 4,6 They also have an important role in maintaining the environment and protecting it. So, in the present study, an attempt was made to assess the knowledge, attitude, and practices among health care personnel toward waste generated.…”
Section: Introductionmentioning
confidence: 99%